(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
Pueblo, (a “coastal village surrounded by lakes, rivers, forests and blue mountains. The sound of the sea used to come with the wind.” p.10) is surely a generic name for the south of Chile, where the author comes from, they pass many unusual things and a multitude of characters with rather strange names such as Calystegia, Eucryphia, Juniperus, Inocybe, Andemansiella to mention just a few. It is the environment of the beliefs and superstitions of the indigenous cultures in these areas under the persistent “southern rain” that Neruda evokes. Thus, the reader is not surprised when smoke arises from a burning land from within or when a person like the Dutchman from Wagner’s Ghost Ship arrives to stay on land while his ship moves away. Witches with their brooms, wizards, and ogres are naturally integrated into this space in a narrative environment that is somewhere between realistic, traditional, and wonderful or Nightmare. You see mysterious lights and scary ugly dwarves, you hear talking animals and you live under the influence of evil spirits.